2005
DOI: 10.1111/j.1444-2906.2005.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of diarrhetic shellfish poisoning toxins, okadaic acid, dinophysistoxin-1, pectenotoxin-6 and yessotoxin in scallops Patinopecten yessoensis

Abstract: Four toxins, okadaic acid (OA), dinophysistoxin-1 (DTX1), pectenotoxin-6 (PTX6), and yessotoxin (YTX), all associated with diarrhetic shellfish poisoning (DSP), were administered via syringe to Scallops Patinopecten yessoensis and their distribution in the hepatopancreas, adductor muscle, and combined other tissues (mantle, gill, gonad) was analyzed by liquid chromatographymass spectrometry. Toxins exclusively remained in the hepatopancreas irrespective of the injection site, adductor muscle or hepatopancreas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Although the Japanese scallop Patinopecten yessoensis lacks the ability to detoxify PTX2 by hydrolyzing it to PTX2sa (Suzuki et al, 1998), PTX2 could be detoxified by an alternative conversion of PTX2 upon the oxidization of the 43-methyl group to the less cytotoxic PTX6 in this species. Our previous study found that the injection of P. yessoensis with PTX6 caused non-toxic symptoms (Suzuki et al, 2005). Thus, the present evaluation of the cytotoxicity of PTX6 is consistent with the results of our previous in vivo experiment on the scallops.…”
Section: Discussionsupporting
confidence: 92%
“…Although the Japanese scallop Patinopecten yessoensis lacks the ability to detoxify PTX2 by hydrolyzing it to PTX2sa (Suzuki et al, 1998), PTX2 could be detoxified by an alternative conversion of PTX2 upon the oxidization of the 43-methyl group to the less cytotoxic PTX6 in this species. Our previous study found that the injection of P. yessoensis with PTX6 caused non-toxic symptoms (Suzuki et al, 2005). Thus, the present evaluation of the cytotoxicity of PTX6 is consistent with the results of our previous in vivo experiment on the scallops.…”
Section: Discussionsupporting
confidence: 92%
“…In Japan, the toxic dinoflagellate Dinophysis fortii , 11 which produces dinophysistoxin‐1 (DTX1) and pectenotoxin‐2 (PTX2), 12 and Protoceratium reticulatum , which produces yessotoxin (YTX), 13,14 are the most important species in the toxic phytoplankton monitoring program for early warning of DSP contamination of bivalves. Whereas DTX1, PTX2, and YTX are the parent toxins in Japanese bivalves, the other toxins are metabolites contained in bivalves 12,15–21 . In the present study, the LC–MS method reported in Quilliam et al .…”
Section: Introductionmentioning
confidence: 59%
“…Whereas DTX1, PTX2, and YTX are the parent toxins in Japanese bivalves, the other toxins are metabolites contained in bivalves. 12,[15][16][17][18][19][20][21] In the present study, the LC-MS method reported in Quilliam et al was modified to quantify major lipophilic toxins associated with DSP in Japanese bivalves. 22 To facilitate this approach to routine monitoring of toxins in bivalves, a divert valve was installed to the LC-MS system to protect the ion source and MS detector from biological matrices in a sequence of analyses of crude 90% methanol sample extracts.…”
Section: Introductionmentioning
confidence: 99%
“…However, what seems now clear is that transformation processes as hydrolysis (during digestion) and, most importantly, acylation are decisive for the metabolism of OA, producing free toxin and esters. Indeed, the rapid bioconversion of OA to 7- O -acyl derivates can be taken as a defense mechanism against this biotoxin, though the hydrophobic nature of the esters may slow their elimination from tissues via body fluid [45]. Although a role in OA acylation was initially ascribed to bacteria present in the bivalve gut [46], it was later demonstrated that in mussels the OA is primarily transformed in the endoplasmic reticulum [47].…”
Section: Response Strategies To Okadaic Acid In Marine Invertebratesmentioning
confidence: 99%